Comparative Study on Biodiversity of Desert National Park Sanctuary and Tal Chhapar Sanctuary - Sh. Praveen Kumar Chandel (International Journal on Orange Technologies, 2022)
Desert National Park is a national park situated in the Indian state of Rajasthan, near the towns of Jaisalmer and Barmer. This is one of the largest national parks, covering an area of 3162 km². The Desert National Park is an excellent example of the ecosystem of the Thar Desert. Sand dunes form around 44% of the Park. The major landform consists of craggy rocks and compact salt lake bottoms, intermedial areas and fixed dunes. The park was gazetted in 1980. Despite a fragile ecosystem, there is an abundance of birdlife. The region is a haven for migratory and resident birds of the desert. Many eagles, harriers, falcons, buzzards, kestrel and vultures are spotted here. Short-toed eagles, tawny eagles, spotted eagles, laggar falcons and kestrels are the most common among these. Sand grouse are spotted near small ponds or lakes. The endangered great Indian bustard is a magnificent bird found in relatively fair numbers. It migrates locally in different seasons. The most suitable time to visit the area is between November and January. The Desert National Park has a collection of fossils of animals and plants which are 180 million years old. Some fossils of dinosaurs which are 60 million years old have been found in the area Tal Chhapar Sanctuary is a sanctuary located in the Churu district of Northwestern Rajasthan, in the Shekhawati region of India. It is known for blackbucks and is also home to a variety of birds. The sanctuary is 210 km from Jaipur on the fringe of the Great Indian Desert and situated on road from Ratangarh to Sujangarh. The Tal Chhapar sanctuary lies in the Sujangarh Tehsil of Churu District. It lies on the Nokha-Sujangarh state highway and is situated at a distance of 85 km from Churu and about 132 km from Bikaner. The nearest railway station is Chappar which lies on Degana-Churu-Rewari line of North Western Railways. The nearest airport is Jaipur which is 215 km from Chappar.